The Transformation of Rural Schools - Carmen Elboj; Amparo Gil; Isabel Rodrigo; Ignacio Zaldívar (Networks: An Online Journal for Teacher Research, 2004)
A rural school is commonly understood as a school that is situated in a rural setting. If we specify a little more, we can say that a school situated in rural surroundings is an educational institution that is supported by rural culture and resources. Additional factors and circumstances exist that if not resolved favorably, can make it difficult to attain those objectives that make this a quality school, with conditions of equality in line with other schools.